Business Ethics - Hindrance or Necessity for Corporate Profitability: An Empirical Corporate Governance Study of US Listed Firms - Dr. Farhan Mahboob (International Journal of Business and Economic Affairs, 2022)
This corporate governance essay seeks to investigate whether business ethics are a hindrance or necessity for corporate profitability? The research analyzes the antagonistic views dividing the world of business ethics, using GLS panel analysis of 943 listed US firms (2005 -2009). Corporate governance is divided into good and questionable governance; their impact, along with the board of directors’ compensation is regressed on pretax income. The results become clearer when controlling for trends in the data, although the model weakens. The results empirically strengthen the arguments that questionable corporate governance has a significant and negative effect on the profitability of the firm; questionable governance hinders profitability. Good corporate governance has a positive but insignificant effect on profitability. The board of directors’ compensation has a significant positive effect on profitability. This study extends the agency theory by providing an avenue for dividing governance into good (GCG) and questionable corporate governance (QCG) and empirical examining their effect on corporate profitability; the study coins a new term Questionable Corporate Governance. The research provides empirical results that questionable corporate governance hampers profitability; as a policy, directors should try to marginalize its use. The research empirically reinforces the belief that firms reap the consequences of the ethics they pursue, thus contributing to the literature on the business ethics and profitability schism.